Examination on acoustic emission partial discharge localization error rate in oil in the presence of pressboard - Mohd Hashim, Ahmad Hafiz; Ahmad, Nur Darina; Azis, Norhafiz; Jasni, Jasronita; Mohd Radzi, Mohd Amran; Masahiro, Kozako; Mohd Jamil, Mohamad Kamarol (IEEE, 2023)
This paper presents an examination on acoustic emission (AE) partial discharge (PD) signal characteristic in oil in the presence of pressboard. First, a test tank was fabricated whereby the PD was generated through needle-plane electrode configuration. Next, the pressboard was placed at the PD source. The electrical PD was measured through Impedance Matching Circuit (IMC) whereby the AE PD signal was measured using AE sensor. Based on the measured AE PD signal, the time of arrival (TOA), amplitude, duration, and distance between PD location and AE sensor was examined. Location error and root mean square error (RMSE) was used to evaluate the PD localization error rate. It is found that the presence of pressboard has an impact on PD localization location error rate and RMSE.